PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN UNTUK KELOMPOK MASYARAKAT (CITIZENSHIP EDUCATION FOR SOCIAL COMMUNITY) - Yuyus Kardiman (Jurnal Ilmiah Mimbar Demokrasi, 2014)
The biggest problems in the Pancasila and Civic Education in fact not on how the Pancasila and Civic Education implemented a formal educational institution, but Pancasila and Civic Education conducted by the non-formal institutions both family and society. More social problems that occur due to the inability of society to educate both by example and efforts to socialize knowledge and values. For this reason the development efforts of Pancasila and Civic Education for the community to be important, especially in Indonesia.